BERFIKIR STATEGIS UNTUK MENCAPAI TUJUAN ORGANISASI DALAM IKLIM GELOMBANG KEKACAUAN (CHAOS) - Arif Arif (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
Strategic thinking becomes the key of success for achieving organization goal. Strategy corresponds to how things are executed based upon set-up plans to gain maximum result. Therefore, organization is obliged to have its own strategy. Four basic principles have emerged in correspondence to new strategy: They have functional roles in human life cycle.